Application of biochar and inorganic phosphorus fertilizer influenced rhizosphere soil characteristics, nodule formation and phytoconstituents of cowpea grown on tropical soil. Issue 10 (October 2020) - Phares, Christian Adler; Atiah, Kofi; Frimpong, Kwame Agyei; Danquah, Andrews; Asare, Aaron T.; Aggor-Woananu, Samira
Abstract: The effect of biochar alone or co-applied with triple superphosphate on rhizosphere soil characteristics, nodule formation, phytoconstituents and antioxidant property of cowpea ( Vigna uguiculata ) is yet to be adequately examined in sub Saharan Africa. A field experiment was conducted where cowpea ( Vigna unguiculata ) was grown in a tropical sandy loam soil amended with biochar at 1.5 t ha −1 and 2.5 t ha −1 solely or together with inorganic phosphate fertilizer (Triple superphosphate), applied at a rate of 60 kg P ha −1 . At 50% flowering, changes in selected rhizosphere soil properties (pH, total nitrogen, available phosphorus, soil organic carbon, cation exchange capacity), nodule count, phytochemicals (phenols, flavonoids, alkaloids, tannins, saponins) and antioxidant property of cowpea roots and leaves were determined by standard laboratory procedures. Differences between means of the measured parameters were established using ANOVA, and relationships among the parameters were explored using Pearson correlation (p < 0.05). Addition of biochar solely or in combination with TSP significantly (p < 0.05) increased soil pH, total nitrogen, available phosphorus, soil organic carbon, cation exchange capacity and root nodule count. Flavonoids, phenols, alkaloids, saponin, tannin contents and antioxidant activity in the roots and leaves were significantly (p < 0.05) higher in the amended soils compared with the unamended soil. Similarly, soil flavonoids, phenols, alkaloids and antioxidant activity were significantly higher in amended soils compared with control. Significant, positive inter and intra correlation with varying strength was found between soil properties, nodule number and phytoconstituents. This is an indication that biochar can be co-applied with triple superphosphate to sustain soil fertility, improve nodulation and enhance concentrations of phytoconstituents in soil, cowpea roots and leaves. Abstract : Biochar, Phytochemicals, Triple superphosphate, Nodule count, Antioxidant activity, Agricultural soil science, Agronomy, Climatology, Ecology, Soil science, Environmental management, Microbiology, Biotechnology, Transcriptomics, Biochemistry.